Lower Anxiety Levels after Counter Pressure Massage in Mother Preparing for Caesarean Section at Tabanan General Hospital - Ni Wayan Putri Sariani; Ni Made Dwi Purnamayanti; Ni Komang Yuni Rahyani (Midwifery Department, Poltekkes Kemenkes Denpasar, Indonesia, 2025)
Anxiety before Caesarean Section surgery will have a bad impact on mother and her fetus. Counter pressure massage is one of complementary therapies that will help reduce the anxiety felt by maternity mothers. This study aims to find out the difference in anxiety levels before and after counter pressure massage in preoperative mothers with Caesarean Section at Tabanan Hospital. This study is classified as pre-experimental with a one-group pretest-posttest design and uses a prospective approach, with a sample of 33 respondents. The sampling technique used is purposive sampling with research instruments in the form of questionnaires. The research was conducted from October to November 2024 in the Maternity Room of Tabanan Hospital. The median of the pretest maternal anxiety level was 13. The median of posttest maternal anxiety level was 7. The data normality test used Kolmogorov-Smirnov, and the data was not normally distributed, then it was continued with a non-parametric statistical test, namely the Wilcoxon test with a nilaai p = 0.000. The conclusion is there is a significant difference between the level of anxiety before and after counter pressure massage in preoperative mothers of Caesarean Section in the Maternity Room of Tabanan Hospital.